Performance Funding as Neoliberal Policy - Natow, Rebecca S.; Dougherty, Kevin J. (International Higher Education, 2019)
Performance funding, a leading example of neoliberal policy making, involves funding institutions not on enrollments but on outcomes such as graduation. This article examines intended and unintended impacts of performance funding and obstacles to making it work effectively. It includes policy recommendations to help institutions better respond to performance funding.